2014
DOI: 10.1097/mao.0000000000000229
|View full text |Cite
|
Sign up to set email alerts
|

A New Comprehensive Cochlear Implant Questionnaire for Measuring Quality of Life After Sequential Bilateral Cochlear Implantation

Abstract: Our preliminary data indicate that this CCIQ is a promising tool in assessing QoL specific to CI2 patients. Overall, patients reported improved QoL, independent of speech perception scores. Further refinements of the questionnaire with larger patient numbers are needed to strengthen the CCIQ.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 21 publications
0
20
0
1
Order By: Relevance
“…Several indirect instruments have been developed to assess the QOL in patients with a cochlear implant and various validation schemes have been presented in the literature [29,30]. Generic instruments to assess the Quality of Life, such as the SF-36 questionnaire, have already been used to assess CI performance.…”
Section: Discussionmentioning
confidence: 99%
“…Several indirect instruments have been developed to assess the QOL in patients with a cochlear implant and various validation schemes have been presented in the literature [29,30]. Generic instruments to assess the Quality of Life, such as the SF-36 questionnaire, have already been used to assess CI performance.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in a study where the additional benefit of a second CI was evaluated, Olze et al (Olze et al, 2012) indicated that HRQoL assessed with the NCIQ further increased after the second CI. With their novel HRQoL questionnaire that assesses physical and psychosocial benefits of sequential bilateral implantation, King et al (King et al, 2014) also demonstrated subjective improvement in all measured domains after receiving a second CI.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, HRQoL measures revealed a positive effect of implantation for unilaterally implanted postlingually deafened elderly patients (Orabi et al, 2006;Sanchez-Cuadrado et al, 2013;Vermeire et al, 2005) and also adult patients implanted for unilateral deafness (Arndt et al, 2011;Vermeire & Van De Heyning, 2009). Recent studies also demonstrate improved HRQoL for bilateral sequential cochlear implantation compared to unilateral implantation (Härkönen et al, 2015;King et al, 2014;Olze et al, 2012).…”
Section: Introductionmentioning
confidence: 94%
“…Sparreboom et al [8] found that sequential bilateral cochlear implantation in children is associated mainly with an improvement in disease-related (speech perception and directional hearing) aspects of QoL. King et al [9], with their new QoL questionnaire that assesses the physical and psychosocial benefits of sequential bilateral cochlear implantation, showed subjective improvement in all measured domainshearing and balance, psychological and social.…”
Section: Introductionmentioning
confidence: 97%